2013
DOI: 10.5539/ibr.v6n12p107
|View full text |Cite
|
Sign up to set email alerts
|

Work Ethics, Work Satisfaction and Organizational Commitment at the Sharia Bank, Indonesia

Abstract: The objective of this study is to examine the effect of work ethics on work satisfaction and organizational commitment at the Sharia Bank. As many as 78 employees became respondents in the study. The data were obtained by utilizing a self-administered questionnaire and in-depth interviews, and analysed using Partial Least Squares (PLS). The findings in the study show that work ethics has a non-significant negative effect on work satisfaction while work ethics has a significant positive effect on organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
4
18
0
2
Order By: Relevance
“…According to the results obtained, results obtained in previous studies are confirmed (Alonso et al, 2010;Anari, 2012;Bartram & Casimir, 2007;Cuadrado & Molero, 2002;Fabi, Lacoursière, & Raymond, 2015;Farahani, Taghadosi, & Behboudi, 2011;Gunlu, Aksarayli, & Sahin Perçin, 2010;Herrera, Torres y Hutiérrez, 2019;Jernigan III et al, 2002;Komari & Djafar, 2013;MR Campbell, 2013;Seyal & Afzaal, 2013;Shurbagi, 2014;Singh & Gupta, 2015;Xirasagar, 2008;Yousaf, Sanders, & Abbas, 2015;Zahari & Shurbagi, 2012;Zayas-Ortiz, Rosario, Marquez, & Gruñeiro, 2015) who evaluated the influence of the transformational leadership style , 32-35. doi:10.1108/HRMID-10-2014-0141 Bartram, T., & Casimir, G. (2007). The relationship between leadership and follower in-role performance and satisfaction with the leader: The mediating effects of empowerment and…”
Section: Conclussionsupporting
confidence: 72%
“…According to the results obtained, results obtained in previous studies are confirmed (Alonso et al, 2010;Anari, 2012;Bartram & Casimir, 2007;Cuadrado & Molero, 2002;Fabi, Lacoursière, & Raymond, 2015;Farahani, Taghadosi, & Behboudi, 2011;Gunlu, Aksarayli, & Sahin Perçin, 2010;Herrera, Torres y Hutiérrez, 2019;Jernigan III et al, 2002;Komari & Djafar, 2013;MR Campbell, 2013;Seyal & Afzaal, 2013;Shurbagi, 2014;Singh & Gupta, 2015;Xirasagar, 2008;Yousaf, Sanders, & Abbas, 2015;Zahari & Shurbagi, 2012;Zayas-Ortiz, Rosario, Marquez, & Gruñeiro, 2015) who evaluated the influence of the transformational leadership style , 32-35. doi:10.1108/HRMID-10-2014-0141 Bartram, T., & Casimir, G. (2007). The relationship between leadership and follower in-role performance and satisfaction with the leader: The mediating effects of empowerment and…”
Section: Conclussionsupporting
confidence: 72%
“…Numerous studies have found that the IWE is closely associated with job satisfaction, e.g. Mohamed, Karim, and Hussein (2010), Yousef (2000), Yousef (2001), Rokhman and Omar (2008), Rokhman (2010), Marri, Sadozai, Zaman, and Ramay (2012), Komari and Djafar (2013), and Gheitani, Imani, Seyyedamiri, and Foroudi (2018). With these arguments, IWE's adoption is required in business operations to bring positive results including job satisfaction.…”
Section: H1 Iwes Is Significantly Related To Organizational Commitmentmentioning
confidence: 99%
“…Herzberg 40 identifies that remuneration is an important resource to satisfy employees' needs; thus, it is one of the hygienic factors associated with labor attitudes. Komari and Djafar 41 identify that employees usually compare their pay with coworkers and interpret pay as a company's concern for them.…”
Section: Salarymentioning
confidence: 99%